2010
DOI: 10.2298/vsp1001019g
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between disease progression and histopathologic criterions of the lip squamous cell carcinoma

Abstract: Histologic and nuclear grade of lip SCC are not prognostic factors for the appearance of the disease relapse and regional lymph node metastases. Tumor size is a predictive factor of the relapse appearance, as well as for lymph node metastases appearance. In clinical practice, tumor size is a factor that classifies patients with lip SCC into the groups of higher and smaller risk of relapse appearance and for lymph node metastases appearance. Our results suggest that, risk for lymph node metastases appearance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Tumour size determines whether tumour will develop into high or low risk group by virtue of recurrence and regional metastasis of lip SCC. As per the review of literature, the possibility for regional metastases increases 2.8 folds with the increase of lip SCC size over 2 cm in diameter (Golubović et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Tumour size determines whether tumour will develop into high or low risk group by virtue of recurrence and regional metastasis of lip SCC. As per the review of literature, the possibility for regional metastases increases 2.8 folds with the increase of lip SCC size over 2 cm in diameter (Golubović et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…It is a factor that allows the distribution of oral cancer patients in groups with a higher or lower risk of recurrence and/or metastatic disease. According to the literature, the risk for regional metastases increases 2.8 times with increasing of lip SCC size over 2 cm in diameter ( 4 ). The authors present the case of a patient with squamous cell carcinoma of the upper lip pointing out the importance of early detection and complete surgical removal of such tumors concerning the fact that this case suggests a higher prognostic significance of the size of the upper lip cancer, as well as the infiltration in tumor-surrounding tissue, mainly the perineural and perivascular spread, than the degree of its histological differentiation for the development of metastatic changes in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a comprehensive study from Israel, SCC is a dominant type of lip cancer, mostly among men aged over 53 and exposed to UV-radiation ( 3 ). In a retrospective–prospective study, epidemiological data showed that in almost half (45%) of the oral cavity SCC cases among the population in Montenegro, both lower and upper lip were affected ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Basic morphological features for estimation of the malignancy level include the histological grade, nuclear grade, mitotic index and nucleocytoplasmic ratio [37][38][39][40]. These parameters are significantly correlated with the degree of tumor infiltration of marginal resection tissue [41,42]. Studies have shown differences in the survival rate of patients with OSC [4][5][6].…”
Section: Markermentioning
confidence: 99%